Energy-Adjusted Dietary Intakes Are Associated with Perceived Barriers to Healthy Eating but Not Food Insecurity or Sports Nutrition Knowledge in a Pilot Study of ROTC Cadets - Daniels, Elizabeth; Hanson, Jennifer Ann (My University, 2021)
Military service is inherently demanding and, due to the nature of these demands, the term “tactical athlete” has been coined to capture the physical requirements of the profession. Reserve Officers’ Training Corps (ROTC) cadets are a unique subset of the military service community, and the complexity of their training and educational pursuits increases their susceptibility to unhealthy eating patterns. The purpose of this pilot study was to explore the relationship between the perceived barriers to healthy eating, food insecurity, sports nutrition knowledge, and dietary patterns among Army ROTC cadets. The usual dietary intake was gathered from (N = 37) cadets using the General Nutrition Assessment Food Frequency Questionnaire. The perceived barriers to healthy eating were measured using a set of scales consisting of social barriers (6 items, α = 0.86), access barriers (2 items, α = 0.95), and personal barriers (2 items, α = 0.67), with higher-scale scores indicating greater perceived barriers. Spearman correlation coefficients were used to measure the association between the energy-adjusted dietary intakes and the scores on the barriers scales. Energy-adjusted intakes of calcium (ρ = −0.47, p ≤ 0.01), fiber (ρ = −0.35, p = 0.03), vitamin A (ρ = −0.46, p ≤ 0.01), vitamin C (ρ = −0.43, p ≤ 0.01), fruit (ρ = −0.34, p = 0.04), and vegetables (ρ = −0.50, p ≤ 0.01) were negatively correlated with the perceived personal barrier scores. The energy-adjusted intakes of fiber (ρ = −0.36, p = 0.03), vitamin C (ρ = −0.37, p = 0.03), and vitamin E (ρ = −0.45, p ≤.01) were negatively correlated with perceived social barriers, while energy-adjusted vitamin C intake was negatively correlated with perceived access barriers (ρ = −0.40, p = 0.01). Although additional research is needed to better understand the dietary patterns of ROTC cadets, among the participants in this study, greater perceived personal, social, and access barriers were associated with less nutrient-dense eating patterns. Interventions aimed at addressing such barriers may prove beneficial for the improvement of diet quality among ROTC cadets.
Keywords: Athletes; Dietary intake; Eating behaviors; Food security; Military personnel; Nutrition knowledge